Late-onset Pompe disease: first clinical description in Russia - S. S. Nikitin; M. O. Kovalchuk; E. U. Zaharova; V. V. Tsivileva (Нервно-мышечные болезни)
Late-onset Pompe-disease (LOPD) is an adult form of the glycogenosis type II. The age of onset ranges from 1 till 75 y.o. and older. The diagnosis of LOPD is based on the presence of trunk and limb-girdle muscle weakness with hyperlordosis, respiratory failure, ocasionally accompanied by cardiomyopathy, persistent mild elevation of creatine kinase, dry blood spot test of the enzyme activity and DNA-analysis of GAA-gene. Early recognition of the LOPD and beginning of the enzyme replacement therapy is important in preventing severe motor and respiratory deficit, the patient disability and in increasing the survival in those patients.